Phenotypic diversity of bread wheat lines with introgressions from the diploid cereal Aegilops speltoides for technological properties of grain and f lour - L. V. Shchukina; I. F. Lapochkina; T. A. Pshenichnikova (Вавиловский журнал генетики и селекции)
The creation of varieties adapted to changing environmental conditions, resistant to various pathogens, and satisfying various grain purposes is impossible without using the genetic diversity of wheat. One of the ways to expand the genetic diversity of wheat is to introduce new variants of genes from the genetic pool of congeners and wild relatives into the genotypes of existing varieties. In this study, we used 10 lines from the Arsenal collection created on the genetic basis of the spring variety ‘Rodina’ and the diploid species Aegilops speltoides in the Federal Research Center “Nemchinovka” in 1994. The lines were previously characterized for the presence of translocations and chromosomal rearrangements cytologically and using molecular markers. Technological analyses were performed on grain obtained in Western Siberia and Moscow region. The aim of this study was to establish the possibilities of expanding the phenotypic diversity for technological properties of grain and flour as a result of such hybridization of bread wheat and the diploid cereal Aegilops speltoides. The variety ‘Rodina’ forms a vitreous grain with a high gluten content in Siberia, but has low physical properties of flour and dough. Five derived lines were found to have significantly higher protein and gluten content in grain. The highest values under both growing conditions were found in lines 73/00i, 82/00i, and 84/00i. Two lines (69/00i and 76/00i) showed a high flour strength and dough elasticity, characterizing the lines as strong and valuable in quality. These lines can be used for baking bread. Line 82/00i inherited from Ae. speltoides a soft-grain endosperm, which indicates the introgression of the Ha-Sp gene, homoeoallelic to the Ha gene of bread wheat, into ‘Rodina’. Flour of this line is suitable for the manufacture of confectionery without the use of technological additives. The lines generally retained their characteristics in different growing conditions. They can be attracted as donors of new alleles of genes that determine the technological properties of grain and resistance to biotic stresses.